2021
DOI: 10.1002/adsc.202100162
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Stereoselective Chloro Sulfoximidations of Terminal Aryl Alkynes Enabled by Copper Catalysis and Visible Light

Abstract: By visible-light photoredox catalysis with copper complexes, sulfoximidoyl chlorides add to terminal aryl alkynes to give the corresponding (E)-β-chlorovinyl sulfoximines with exclusive regio-and stereoselectivities in high yields. Two representative products have been characterized by X-ray crystal structure analysis. Radicals appear to be decisive intermediates. As demonstrated by two subsequent reactions, the products can be derivatized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…It starts with a homolytic sulfur chlorine bond cleavage of 1 leading to radical A and atomic chlorine. As described above, analogous bond breavage reactions are known, 13,14 but in contrast to those previous processes, where significant quantities of metal catalysts had to be added, the current protocol makes use of trace amounts of stainless steel particles of the milling device and their catalytic activity under mechanochemical conditions. Once radical A is formed, it adds to allene 2 providing a very stable substituted allyl radical B. Chlorination of B with 1 pro-vides product 3 and continues the radical chain process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It starts with a homolytic sulfur chlorine bond cleavage of 1 leading to radical A and atomic chlorine. As described above, analogous bond breavage reactions are known, 13,14 but in contrast to those previous processes, where significant quantities of metal catalysts had to be added, the current protocol makes use of trace amounts of stainless steel particles of the milling device and their catalytic activity under mechanochemical conditions. Once radical A is formed, it adds to allene 2 providing a very stable substituted allyl radical B. Chlorination of B with 1 pro-vides product 3 and continues the radical chain process.…”
Section: Resultsmentioning
confidence: 99%
“…12 In this context, we recently demonstrated copper/photoredox-catalysed additions of sulfoximidoyl chlorides 1 to arylalkynes leading to highly substituted S-vinyl derivatives (Scheme 1, top). 13 Under similar conditions using a ruthenium catalyst and blue light, β-keto sulfoximines were obtained (Scheme 1, middle). 14 Our background in mechanochemistry made us wonder, if such radical addition reactions starting from sulfoximidoyl chlorides 1 could also be initiated by mechanical energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Bolm and co-workers developed the visible-light-induced synthesis of substituted ( E )-β-chlorovinyl sulfoximines 131 from aromatic terminal alkynes 18 with the aid of copper photoredox catalysts (Scheme 45). 41 The model substrates for the optimization studies included the reaction of N -tosyl-protected sulfoximidoyl chloride with phenyl acetylene. The optimization studies revealed that the use of 10 mol% copper( i ) chloride as the catalyst in combination with 20 mol% of dmbp (6,6-dimethyl-2,2-bipyridine) ligand in DCM as solvent at room temperature under blue LED irradiation afforded the desired products in moderate to good yields.…”
Section: Functionalization Of Alkynes Using Copper Catalystsmentioning
confidence: 99%
“…Sulfoximines have extensively found use in synthesis, agricultural science, and medicinal chemistry . Recently, we reported a new synthesis of functionalized sulfoximines through alkyne additions of sulfoximidoyl radicals generated from sulfoximidoyl chlorides by copper catalysis . Today, the same starting materials react differently when subjected to blue light in air.…”
mentioning
confidence: 99%